Cost-effectiveness of durvalumab plus tremelimumab in combination with chemotherapy for the treatment of metastatic non-small-cell lung cancer from the US healthcare sector’s and societal perspectives - Gan, Yena; Shi, Fenghao; Zhu, He; Li, Huangqianyu; Han, Sheng; Li, Duoduo (Frontiers in Pharmacology, 2024)
Purpose: Metastatic non-small cell lung cancer (mNSCLC) has a high incidence rate, and economic burdens to patients, health care systems, and societies. Durvalumab plus tremelimumab and chemotherapy (T+D+CT) is a novel therapeutic strategy for mNSCLC, which demonstrated promising efficacy in a phase-3 randomized clinical trial, but its economic value remains unclear.Methods: This economic evaluation used a hypothetical cohort of patients with mNSCLC, with characteristics mirroring those of the participants in the POSEIDON trial. Several partitioned survival models were constructed to estimate 15-year costs and health outcomes associated with the T+D+CT, durvalumab plus chemotherapy (D+CT) and chemotherapy alone (CT) strategies, discounting costs and effectiveness at 3% annually. Costs were in 2023 US dollars. Data were derived from the POSEIDON trial and published literature. Deterministic and probabilistic sensitivity analyses were performed to assess the uncertainty of input parameters and study generalizability. The analysis was designed and conducted from September 2022 to March 2023. To evaluate the costeffectiveness of T+D+CT, compared with CT and D+CT, for mNSCLC from the perspectives of the US health care sector and society.